From Natural Semantics to Abstract Machines - Ager, Mads Sig (BRICS Report Series, 2004)
We describe how to construct correct abstract machines from the class of L-attributed natural semantics introduced by Ibraheem and Schmidt at HOOTS 1997. The construction produces stack-based abstract machines where the stack contains evaluation contexts. It is defined directly on the natural semantics rules. We formalize it as an extraction algorithm and we prove that the algorithm produces abstract machines that are equivalent to the original natural semantics. We illustrate the algorithm by extracting abstract machines from natural semantics for call-by-value, call-by-name, and call-by-need evaluation of lambda terms.